2015
DOI: 10.1007/s00209-015-1459-y
|View full text |Cite
|
Sign up to set email alerts
|

Fragility and persistence of leafwise intersections

Abstract: In this paper we study the question of fragility and robustness of leafwise intersections of coisotropic submanifolds. Namely, we construct a closed hypersurface and a sequence of Hamiltonians C 0 -converging to zero such that the hypersurface and its images have no leafwise intersections, showing that some form of the contact type condition on the hypersurface is necessary in several persistence results. In connection with recent results in continuous symplectic topology, we also show that C 0 -convergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Since then various forms or generalizations of it were studied. See [19,16,25], [1, §1.1] and [34, §1.4] and references therein for the brief history of these problems.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then various forms or generalizations of it were studied. See [19,16,25], [1, §1.1] and [34, §1.4] and references therein for the brief history of these problems.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Remark 1.30. Recently, Ginzburg and Gürel [25] showed that there exists a closed, smooth hypersurface S ⊂ R 2n , 2n ≥ 4, and a sequence of C ∞ -smooth autonomous Hamiltonian F k → 0 in C 0 , supported in the same compact set, such that S and ϕ F k (S) have no leafwise intersections. It suggests that Theorem 1.29 is best possible in one sense.…”
Section: Applications To Hamiltonian Dynamicsmentioning
confidence: 99%
“…V. L. Ginzburg and B. Z. Gürel [GG,Theorem 1.1] recently proved that for n ≥ 2 there exists a closed smooth hypersurface N ⊆ R 2n and a compact subset K ⊆ R 2n , such that for every ε > 0 there exists a smooth function…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The To see that this operator is well-defined, recall that it is defined on the direct sum of Z 2 's indexed by the set occurring on the right hand side of (6). 10 Using the 7 By definition, for every such point x 0 , the point x(1) = ϕ 1 (x 0 ) lies in the isotropic leaf of x 0 . Hence x 0 is a leafwise fixed point of ϕ 1 .…”
mentioning
confidence: 99%